Analysis of Raw Material Inventory in Peuyeum Business Mr. Marsan in Batujaya Sub-District, Karawang - Linawati, Linawati; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Westscience Press, 2024)
This study aims to determine how the inventory of peuyeum raw materials and how to anticipate the quality mismatch of peuyeum raw materials in supporting the continuity of Mr. Marsan's peuyeum business. This research method using descriptive qualitative. Data collection through interviews with Mr. Marsan, direct observation, and document analysis related to raw material inventory. The result of this study is that sufficient supply of raw materials according to needs can facilitate the production process and can produce quality products. There are four raw material suppliers who work with Mr. Marsan, namely Bogor, Subang, Sukabumi, and Lampung. Of course, the prices offered from each supplier are different. Bogor with a price of Rp2,200, Sukabumi Rp2,300, Subang Rp2,150, and Lampung with a price of Rp2,500. Suppliers have their own advantages and disadvantages. Of these advantages and disadvantages, Bogor and Subang are the main suppliers. Bogor and Subang were chosen to be the main suppliers because they offer lower prices, the quality of cassava that suits the needs, in addition to the close delivery distance. With these advantages, cassava from Bogor and Subang is often the first choice compared to Sukabumi and Lampung. In preventing or reducing the risk of raw material quality mismatches, there are several efforts made, one of which is by sorting or checking each raw material sent before production.